LANGUAGE PATTERNS IN THE LINGUISTC LANDSCAPE OF PESANTREN - Kamal Yusuf (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
We often see writings or texts in public spaces, commonly referred to as the linguistic landscape, including educational public spaces. Islamic boarding schools or institute that are places of education are inseparable from the existence of the linguistic landscape. This research on the linguistic landscape of the Linguistic Landscape taken from the area of the Pesantren An Nuqayah, Guluk-Guluk, Madura aims to learn more about the use of the linguistic landscape in Islamic boarding schools, especially the well-known institute in Madura. The method used to analyze the presence of the linguistic landscape in this Islamic boarding school is a mixed one. The results of the observation indicated that the use of forms written in the Indonesian language is still prevalent, followed by the use of forms written in foreign languages such as Arabic and English. This is very common because education in Indonesia in general still uses the language of the nation's unity, although of course it does not forget the importance of foreign languages, especially international languages.